Information to Improve Public Perceptions of the Food and Drug Administration (FDA’s) Tobacco Regulatory Role - Osman, Amira (Int J Environ Res Public Health, 2018)
While the Food and Drug Administration (FDA) has had regulatory authority over tobacco products since 2009, public awareness of this authority remains limited. This research examines several broad types of information about FDA tobacco regulatory mission that may improve the perceptions of FDA as a tobacco regulator. Using Amazon Mechanical Turk, 1766 adults, smokers and non-smokers, were randomly assigned to view a statement about FDA regulatory authority that varied three information types in a 2 × 2 × 2 between subjects experimental design: (1) FDA’s roles in regulating tobacco (yes/no); (2) The scientific basis of regulations (yes/no); and (3) A potential protective function of regulations (yes/no). Using factorial ANOVA, we estimated the main and interactive effects of all three types of information and of smoking status on the perceptions of FDA. Participants that were exposed to information on FDA roles reported higher FDA credibility and a greater perceived knowledge of FDA than those who did not. Exposure to information about the scientific basis of regulations led to more negative views of the tobacco industry. Participants who learned of the FDA’s commitment to protecting the public reported higher FDA credibility and more positive attitudes toward regulations than those who did not learn of this commitment. We observed no significant interaction effects. The findings suggest that providing information about the regulatory roles and protective characterization of the FDA’s tobacco regulatory mission positively influence public perceptions of FDA and tobacco regulations.